Ethernet in the first mile : - Beck, Michael (McGraw-Hill, 2005)
IEEE standard 802.3, Ethernet in the First Mile (EFM), approved this July, standardizes broadband Ethernet, allowing service providers to focus on providing critical broadband services without worrying about interoperability conflicts. This book will annotate and explain the dense language of the standard document, taking particular care how to explain how the EFM dovetails with other standards. For engineers struggling with the standard, this book will show clearly how each piece is supposed to work in the real world.